SISTEM PERTANGGUNGJAWABAN PIDANA PADA TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA - Titik Suharti (Perspektif, 2006)
System of code penal responsibility at crime hardness in house hold, has arranged UU No. 23 Th. 2004. it’s scope: physicall hardness, psychological hardness, sex hardness and it’s let house hold.